2022
DOI: 10.1002/ijgo.14236
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and causes of severe maternal outcomes in Somaliland using the sub‐Saharan Africa maternal near‐miss criteria: A prospective cross‐sectional study in a national referral hospital

Abstract: Objective: To describe the incidence and causes of severe maternal outcomes and the unmet need for life-saving obstetric interventions among women admitted for delivery in a referral hospital in Somaliland. Methods:A prospective cross-sectional study was conducted from April 15, 2019 to March 31, 2020, with women admitted during pregnancy or childbirth or within 42 days after delivery. Data were collected using the World Health Organization (WHO) and sub-Saharan Africa (SSA) maternal near-miss (MNM) tools. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
8
3
Order By: Relevance
“…From the original maternal near-miss study including 6,658 women [ 14 ], 1255 women underwent a CS and were included in the analyses ( Figure 1 ). Among the total number of women included, 429 (34.2%) did not experience CS delay, 237 (18.9%) experienced CS delay ranging from one hour to less than three hours, and 594 (43.3%) experienced CS delay of three hours and over.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the original maternal near-miss study including 6,658 women [ 14 ], 1255 women underwent a CS and were included in the analyses ( Figure 1 ). Among the total number of women included, 429 (34.2%) did not experience CS delay, 237 (18.9%) experienced CS delay ranging from one hour to less than three hours, and 594 (43.3%) experienced CS delay of three hours and over.…”
Section: Resultsmentioning
confidence: 99%
“…For the current study, we used a prospective cohort study design nested in a larger maternal near-miss (MNM) study ( n = 6658) reported elsewhere [ 14 ]. The study was reported in accordance with the Strengthening of Reporting of Observational Studies in Epidemiology (STROBE) guidelines of cohort studies [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The leading causes of maternal deaths are postpartum haemorrhage, pre-eclampsia/eclampsia, prolonged and obstructed labour and infections combined with limited access to SRH services. [10][11][12] The recent Somaliland Health and Demographic Report (2020) showed that 67% of children are delivered at home, further contributing to high maternal and neonatal mortality and morbidity. Moreover, cultural practices such as female genital mutilation/cutting (FGM/C) are prevalent.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Somaliland has a high annual maternal mortality rate, at an estimated 396 deaths per 100 000 live births 10. The leading causes of maternal deaths are postpartum haemorrhage, pre-eclampsia/eclampsia, prolonged and obstructed labour and infections combined with limited access to SRH services 10–12. The recent Somaliland Health and Demographic Report (2020) showed that 67% of children are delivered at home, further contributing to high maternal and neonatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%